The role of health literacy in intervention studies targeting children living with overweight or obesity and their parents—a systematic mixed methods review - Holmen, Heidi; Flølo, Tone Nygaard; Tørris, Christine; Torbjørnsen, Astrid; Almendingen, Kari; Riiser, Kirsti (Frontiers in Pediatrics, 2025)
BackgroundExcess weight and obesity are increasing among children. Health literacy has been suggested as a feasible concept for enabling informed health choices in weight management interventions for children and their parents. Knowledge of the skills necessary for a child to maintain new health behaviors is limited and the role of health literacy remains unclear. Thus, there is a need to summarize the effects of and experiences with interventions that include health literacy components to guide the development of effective, future weight-related interventions.AimThis review aims to identify how health literacy is integrated into studies of interventions targeting children with excess weight or obesity and/or their parents and to appraise the identified literature.MethodsWe conducted a systematic mixed methods review, with searches in Medline, CINAHL, Cochrane, EMBASE, ERIC, PsycINFO, and Web of Science. We included studies of interventions published after 2013 that targeted children under 19 years with excess weight or obesity and/or their parents, where health literacy played a role. Results from the included studies were integrated using qualitative data transformation techniques, followed by a narrative summary.ResultsWe identified 7,910 citations. Four reports met our inclusion criteria and were included for review. These reports included a total of 402 children. Health literacy was assessed at baseline in two studies and measured as an outcome over time in one study. Methodological quality varied among the retained reports, with differences observed in study design, risk of bias and data collection methods. The reports highlight the need to adapt weight management treatments to the individual level of health literacy in children and their families to first ensure active participation in their treatment and second ensure long-term compliance with necessary lifestyle-related changes.DiscussionSurprisingly, little attention has been paid to the importance of health literacy in weight management programs targeting children and their families. Seemingly, treatments tailored to the individual level of health literacy have not been prioritized in research. Addressing health literacy in children's weight management continues to be a multifaceted and ambitious mission. Future research should focus on integrating health literacy into weight management interventions in a systematic and theory-driven manner, ensuring that these interventions are tailored to the specific needs of children and their families and can sustain behavior change over time.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=478957, identifier: CRD42023478957.